Smoking and periodontal disease: Clinical evidence for an association - Moimaz, Suzely Adas Saliba [UNESP]; Zina, Lívia Guimarães [UNESP]; Saliba, Orlando [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (My University, 2009)
Purpose: The aim of the present study was to assess the periodontal condition and smoking status, according to dose and duration information, and to estimate the percentage of subjects with periodontitis attributable to cigarette smoking in a representative adult rural population in southern Brazil. Materials and Methods: Bivariate statistical analysis was used to evaluate the association of smoking status with periodontitis in a cross-sectional study comprising 165 dentate individuals, aged 35 to 66 years, subjected to oral clinical examination of six sites per tooth in all sextants. Results: The prevalence of periodontitis (having ≥ 1 pocket of ≥ 4 mm around the index teeth) in the population was 35.2%. Overall, 13.9% had a cumulative loss of attachment > 4 mm; 35.7% of subjects were current smokers, classified as heavy (average 25.3 pack years), moderate (average 14.6 pack years) and light smokers (average 3.1 pack years). Statistical analysis showed that current smokers had an 11 times (95% confidence interval [CI] = 4.69 to 26.62) and former smokers had a nine times (95% CI = 3.29 to 25.96) greater probability of having established periodontitis compared with non-smokers. The number of pack years (P = 0.0004) and years of smoking exposure (P = 0.0013) were associated with an increased prevalence of periodontitis. The number of current smokers with periodontitis might be reduced by 80%, had they not smoked cigarettes. Of the subjects with periodontitis, 64% could be prevented among current smokers by eliminating tobacco consumption. Conclusions: Cigarette smoking was strongly associated with periodontitis, and there was a relationship with dose and duration of smoking. These findings contributed to the evidence of smoking as a risk factor for periodontal disease and support the importance of dose-response analysis on determining the strength of this association.
Keywords: Periodontal diseases; Primary prevention; Risk factors; Smoking